An exploration of high-performance team sport coaches` pedagogical practice across a season: A mixed-methods case study approach - O`Mahony, N.; Sherwin, I.; Lyons, M.; Kearney, P. E. (Sports Coaching Review, 2025)
This study explored high-performance team sports coaches` pedagogical practice in light of Game-Based Approach (GBA) pedagogy. A mixed-methods, longitudinal case study explored two high-performance Gaelic football coaches` perceptions of their practice through multiple semi-structured and stimulated recall interviews which were supported by systematic observation of practice sessions (n = 52). The coaches` espoused use of GBA pedagogy strongly aligned with their actual practice incorporating scaffolding principles fundamental to constructivist learning theory. They also displayed a critically reflective rationale for the judicious deviation from highly representative playing form activity considering the needs of the players and the specificities of their context. This study reinforces the importance of critical, adaptable, and context-driven coaching practices that bridge the gap between pedagogical models and real-world applications. Coach developers should facilitate collaborative in-situ support to assist coaches` critical reflection on the application of GBAs to their specific contexts.